(untitled) (Research, Society and Development, 2021)
Staphylococcus aureus is a pathogenic bacterium that can cause many diseases in humans and animals. The use of antibiotics to control their development has often been inefficient owing to their ability to become resistant to these substances. Thus, a search for new effective alternatives to combat this microorganism is a challenge for science and has become extremely relevant. This study aimed to analyze in the literature the use of different substances, natural and chemicals, in the control of the development of S. aureus from different sources. For this study, books, dissertations, thesis and scientific articles from the Google academic, Scielo and Science direct databases were used. The works were selected austerely, according to the content of the title and / or abstract. Based on the results found that the use of antibiotics, despite being an efficient way to control the development of S. aureus, their use must be controlled due to the occurrence of resistant strains to these substances. Other possibilities for the control of this microorganism have shown efficiency, such as the use of essential oils, plant extracts, biofilms, gelatin-based films, biological control by lytic bacteriophages and ozone therapy. However, to use these substances, further studies must be performed.